Microdebrider Assisted Endoscopic versus Conventional Sinus Surgery in Sinonasal Polyposis: A Comparative Study : Microdebrider Assisted Endoscopic versus Conventional Sinus Surgery - Khalily, Waqas; Durrani, Aamna; Syed, Sarwat Hassan; Naveed, Amir; Qazi, Zia Us Salam; Qamar, Sabih (Pakistan Journal of Health Sciences, 2024)
For sinonasal polyposis, functional endoscopic sinus surgery or conventional is the standard surgical approach. Microdebrider assisted endoscopic sinus surgery provides patients with a better therapeutic approach. Objective: To assess and compare intraoperative, loss of smell, synechiae formation and polyp recurrence between microdebrider and conventional method in nasal polyposis patients. Methods: Cohort Study was carried out in Department of Ear Nose Throat, Shaikh Zayed Hospital, Lahore, 2022-2023. A total of sixty individuals with sinonasal polyposis, presenting in both genders, were included. Once written consent was obtained, the patient's comprehensive demographics were documented. Every patient was split evenly into two groups. Thirty patients each from Group A and Group B underwent endoscopic sinus surgery using traditional endoscopic tools and microdebrider respectively. Results were compared between the two groups in terms of synechiae production, length of operation, postoperative crusting, loss of smell, and intraoperative blood loss. Results: Age and gender differences between the two groups were not statistically significant (p-value >0.05). Regarding synechiae and loss of scent, there was no discernible difference between the two groups. Conclusions: The endoscopic sinus surgery with microdebrider was more effective for sinonasal polyposis as compared to conventional procedure